2015
DOI: 10.1158/2326-6066.cir-15-0141
|View full text |Cite
|
Sign up to set email alerts
|

Subacute CNS Demyelination after Treatment with Nivolumab for Melanoma

Abstract: Immunotherapy with monoclonal antibodies targeting cytotoxic T-lymphocyte antigen 4 (CTLA-4) or programmed cell death 1 (PD-1) has improved the survival of patients with metastatic melanoma. These agents carry a certain risk of adverse immune-related events. We present a patient with widely metastatic melanoma who was initially treated with ipilimumab and subsequently with nivolumab. After four infusions of nivolumab, he developed subacute multifocal central nervous system (CNS) demyelination. Nivolumab was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 19 publications
2
50
1
Order By: Relevance
“…Withdrawal of immune checkpoint inhibitors and initiation of intravenous methylprednisolone sodium succinate (equivalent to 1000 mg of methylprednisolone) for 5 days, 0.4 mg/kg/day of intravenous immunoglobulin for 5 days, and two doses of rituximab (1000 mg) in one patient, and only oral prednisone (60 mg/day) in the other, resulted in dramatic improvement of neurologic symptoms. 5 Similarly, Maurice et al 10 reported a case of AIE with demyelination findings in MRI, like in our case, but the patient was treated for malignant melanoma and had received ipilimumab prior to nivolumab therapy. The patient initially responded very well with IVIG and steroid, but unfortunately died later because of progressive AIE.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Withdrawal of immune checkpoint inhibitors and initiation of intravenous methylprednisolone sodium succinate (equivalent to 1000 mg of methylprednisolone) for 5 days, 0.4 mg/kg/day of intravenous immunoglobulin for 5 days, and two doses of rituximab (1000 mg) in one patient, and only oral prednisone (60 mg/day) in the other, resulted in dramatic improvement of neurologic symptoms. 5 Similarly, Maurice et al 10 reported a case of AIE with demyelination findings in MRI, like in our case, but the patient was treated for malignant melanoma and had received ipilimumab prior to nivolumab therapy. The patient initially responded very well with IVIG and steroid, but unfortunately died later because of progressive AIE.…”
Section: Discussionsupporting
confidence: 74%
“…15 Data obtained from all cases reported on nivolumab induced CNS toxicities correlates with the findings by Sznol et al, 7 who demonstrated that side effects can occur more frequently with combination of checkpoint inhibitors, such as nivolumab plus ipilimumab, and can occur earlier than historical experience with either agent alone. 10 Nivolumab has indications from the National Cancer Institute to be used during or after platinum chemotherapy in several cancers, and effects of worsening disease or previous drug therapy could contribute to neurotoxicity. 16 Currently, there is no tool to predict who will develop neurotoxicity after receiving a PD-1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple reports of autoimmune neurologic side effects of checkpoint inhibitors including hypophysitis, encephalitis, demyelinating polyneuropathy and encephalomyelitis. 128135 These can often be completely reversible, particularly if recognized and treated early, however several deaths secondary to autoimmune toxicity have been reported. There have also been two case reports, one with melanoma and the other with NSCLC, who 1–2 months after treatment with PD-1 inhibitors had biopsy-confirmed delayed radiation-induced vasculitic leukoencephalopathy.…”
Section: Immune Checkpointsmentioning
confidence: 99%
“…In a retrospective analysis of data pooled from 148 melanoma patients treated with nivolumab alone or nivolumab plus peptide vaccine, Freeman-Keller et al reported immune-related adverse events in 68.2% of patients; however, grade III/IV adverse events including rash, asymptomatic elevation in amylase/lipase, and colitis, were rarely found [66] . Maurice et al reported the case of a metastatic melanoma patient, initially treated with ipilimumab and then, with infusions of nivolumab, who developed subacute multifocal central nervous system (CNS) demyelination and succumbed to his CNS lesions 4 months later despite discontinuation of nivolumab [67] . Kato et al [68] have observed the exacerbation of pso- riasis vulgaris during nivolumab for oral mucosal melanoma, whereas Matsumara et al [69] have reported the exacerbation of psoriasis during nivolumab therapy for metastatic melanoma.…”
Section: Nivolumab Safetymentioning
confidence: 99%